Analisis Tingkat Efektivitas dan Efisiensi Penggunaan Anggaran Belanja Tahun 2020 – 2024 Pada Pemerintah Kabupaten Madiun (Studi Kasus pada Badan Pengelolaan Keuangan dan Aset Daerah) - Prabowo, Hernanda Bagus; Diana, Nur; Afifudin, Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2025)
This study aims to analyze the level of effectiveness and efficiency of budget use at the Madiun Regency Regional Financial and Asset Management Agency during the 2020-2025 period. This study applies a qualitative descriptive approach method with data collection through interviews with agency sources and review of documentation recording the results of budget realization reports. The results show that the assessment of the level of effectiveness of budget use in 2020 is categorized as less effective with a percentage level of 77%, in 2021-2024 it is categorized as effective with percentage levels of 96%, 96%, 97%, and 98%. For the assessment of the level of efficiency of budget use in 2020 it is categorized as efficient with a percentage level of 78%, in 2021-2024 it is categorized as very effective with percentage levels of 7%, 7%, 8% and 8%. The causes of the level of effectiveness and efficiency of budget use are due to the Covid-19 outbreak, changes in the regulations of the Minister of Home Affairs and changes in policy regulations. This study provides a new, clearer picture regarding the analysis of the level of effectiveness and efficiency of budget use in 2020-2024.Keywords : Budget, effectiveness, efficiency